Principles of Transactive Computer-Supported Collaboration Scripts - Armin Weinberger (Universitetsforlaget, 2011)
Parts of the classroom of the future may be built online allowing for computer-supported collaborative learning (CSCL). A central challenge in CSCL is a lack of transactivity, i.e., learners have problems building on the reasoning of their peers. A means of fostering CSCL are scripts that specify, sequence, and distribute roles and activities among a group of (online) learners. This article identifies five instructional design principles that explain script effects and inform script design: 1) regulation of learning activities; 2) complementary procedural knowledge; 3) process-oriented instruction; 4) substitution of coordination efforts; and 5) awareness induction. Keywords: Computer-supported collaboration scripts, CSCL, transactivity